Materials for molecular electronics and magnetism. Issue 33 (17th August 2021) - Biscarini, Fabio; Coronado, Eugenio; Painelli, Anna; Yamashita, Masahiro
Abstract : Fabio Biscarini, Eugenio Coronado, Anna Painelli and Masahiro Yamashita introduce the Journal of Materials Chemistry C themed issue on Materials for Molecular Electronics and Magnetism, in honour of Jaume Veciana and Concepció Rovira. Abstract : Functional molecular materials exhibiting, in particular, electrical, magnetic or optical properties have been an active focus of research over the last 50 years. These materials have been a source of inspiration in two interrelated areas of research, namely, molecular electronics and molecular magnetism, with important implications in biomedical areas. This themed issue highlights recent progress and perspectives in these important areas of materials science. The issue covers topics from the chemical design and manipulation of novel molecular materials with unprecedented control over their properties, even at the single-molecule level, to exciting applications of these special molecular systems in emerging fields, including bioelectronics and molecular spintronics.